Engineering a serum response factor superactivator of smooth muscle gene expression with a condensate-forming domain - Peiheng Gan; Xinyi Zhou; Akansha M. Shah; Svetlana Bezprozvannaya; Kenian Chen; Qianqian Ding; Hui Li; Lin Xu; Ning Liu; Eric N. Olson (Proceedings of the National Academy of Sciences, 2025)
Differentiation of smooth muscle cells (SMCs) is driven by the activation of a set of genes controlled by serum response factor (SRF), a ubiquitous transcription factor with limited intrinsic transcriptional activity. Myocardin (MYOCD) is a strong transcriptional coactivator that orchestrates smooth muscle differentiation through its association with SRF. MYOCD forms nuclear condensates via its intrinsically disordered transcription activation domain (TAD), whereas SRF is diffusely distributed in the nucleus. MYOCD recruits SRF into these condensates, thereby activating the smooth muscle gene program. We engineered a “superactivator” of smooth muscle genes by replacing SRF’s weak TAD with that of MYOCD, thereby enabling SRF to form nuclear condensates and reprogram fibroblasts into SMCs. Using protein proximity labeling, quantitative proteomics and superresolution confocal microscopy, we show that condensates formed by the MYOCD TAD aggregate chromatin remodelers, RNA polymerases, and mRNA processing factors to drive smooth muscle gene expression. These findings provide insights into the mechanisms whereby nuclear condensates facilitate tissue-specific gene expression and highlight a strategy for engineering cell fate determinants by coupling condensate-forming domains to heterologous DNA-binding proteins.